Next generation sequencing and array-based comparative genomic hybridization for molecular diagnosis of pediatric endocrine disorders - Maki Fukami; Mami Miyado (Annals of Pediatric Endocrinology & Metabolism, 2017)
Next-generation sequencing (NGS) and array-based comparative genomic hybridization (array CGH) have enabled us to perform high-throughput mutation screening and genome-wide copy number analysis, respectively. These methods can be used for molecular diagnosis of pediatric endocrine disorders. NGS has determined the frequency and phenotypic variation of mutations in several disease-associated genes. Furthermore, whole exome analysis using NGS has successfully identified several novel causative genes for endocrine disorders. Array CGH is currently used as the standard procedure for molecular cytogenetic analysis. Array CGH can detect various submicroscopic genomic rearrangements involving exons or enhancers of disease-associated genes. This review introduces some examples of the use of NGS and array CGH for the molecular diagnosis of pediatric endocrine disorders.